A review of the current state of natural biomaterials in wound healing applications - Ansari, Mojtaba; Darvishi, Ahmad (Frontiers in Bioengineering and Biotechnology, 2024)
Skin, the largest biological organ, consists of three main parts: the epidermis, dermis, and subcutaneous tissue. Wounds are abnormal wounds in various forms, such as lacerations, burns, chronic wounds, diabetic wounds, acute wounds, and fractures. The wound healing process is dynamic, complex, and lengthy in four stages involving cells, macrophages, and growth factors. Wound dressing refers to a substance that covers the surface of a wound to prevent infection and secondary damage. Biomaterials applied in wound management have advanced significantly. Natural biomaterials are increasingly used due to their advantages including biomimicry of ECM, convenient accessibility, and involvement in native wound healing. However, there are still limitations such as low mechanical properties and expensive extraction methods. Therefore, their combination with synthetic biomaterials and/or adding bioactive agents has become an option for researchers in this field. In the present study, the stages of natural wound healing and the effect of biomaterials on its direction, type, and level will be investigated. Then, different types of polysaccharides and proteins were selected as desirable natural biomaterials, polymers as synthetic biomaterials with variable and suitable properties, and bioactive agents as effective additives. In the following, the structure of selected biomaterials, their extraction and production methods, their participation in wound healing, and quality control techniques of biomaterials-based wound dressings will be discussed.